Twelve experiences of digital identity - Jiménez Vivas, Javier Eduardo (2023)
The digital transformation is reaching the individual and society in all its magnitude. Identity is an element that relates the first to the second, allows people to interact with each other within society and makes it possible to establish all kinds of relationships with people, organisations, the State, etc. These facets are developing within the environment of digital transformation and are therefore generating different forms of digital identity. We find them in the exercise of fundamental rights, our official documentation, judicial decisions, modern technologies, social networks, and we will see them develop in greater number and depth. This work bears witness to the variants that digital identity is taking on, and proposes a reflection on the criteria that will allow us to understand future aspects of the digitalisation of our identity.